Unpublished examples of lead miniature vessels from Turkey - Laflı, Ergün; Buora, Maurizio (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2024)
In this brief paper we focus on 24 previously unpublished lead miniature vessels from the Archaeological Museums of Adana, Mersin, Kahramanmaraş and Şanlıurfa (ancient Edessa) in southern and south-eastern Turkey as well as the Museums of Marmaris, Bodrum and Ephesus in western Turkey. These lead objects date from the Roman or Late Roman-Early Byzantine periods, and typologically most of them are in the form of miniature amphorae. This group of small containers from Turkey are only limitedly known through an article of us which is published in 2022. With these 20 new examples that will be presented here for the first time we extend our corpus with adding four other, earlier bottles from Kahramanmaraş as their Iron Age predecessors. In the Roman Near East they are mostly known from Jerusalem and some other sites in Israel. In this paper we will especially deal with the function, typology and distribution of these objects in Asia Minor.